Influence of Environmental Factors on Chronic Kidney Disease - Fatukasi, Joseph Irewole; Badeji-Ajisafe, Bukola; Agbaje, Olanrewaju A.; Ajibade, Abimbola O; Ajibade, Idowu V; Ojo, Olalekan O; Sarumi, Oluwafemi (British Journal of Healthcare and Medical Research, 2023)
Chronic kidney disease (CKD) is one of the health challenges ravaging the world presently with significant morbidity and mortality as well as enormous health cost. Some factors are associated with increased risk of having CKD including age, gender and environmental factors such as certain occupations. This research aims to look at the age, sex and occupational distribution of patients with CKD at a tertiary hospital in Owo, Ondo State, Nigeria. The survey design gathered from the 86 dataset collected from patients with chronic renal disease attending the renal clinic. The results show that the highest age of respondents that have kidney disease is 35years. Also, trading is the most prominent occupation in patients with kidney disease. The major symptom of kidney disease is decreased urine output. The result also revealed that gender is statistically significant F(4,85) =5.816, P<0.05. Also, the result shows that age is significant to kidney disease. F(4,85) =8.225,P<0.05. Likewise, results revealed that occupation is not significant F(3,85) =1.068, P>0.05 for kidney diseases. Further results reveal a linear relationship between the three predictors (age, gender, and occupation). They significantly predicted the criterion variable F(3,85) =7.293 and accounted for 21.1% observed variance in kidney disease. Age β=.561,t(86)=3.038P<0.05) and gender (β=.860, t(86)=4.468, P˃0.05).It has made a significant contribution to the model where gender was the most potent predictor. Based on the findings, it was concluded that age and gender have an effect on kidney disease.